Time-varying formation prescribed performance control with collision avoidance for multi-agent systems subject to mismatched disturbances - Zheng, Chang-Bing; Pang, Zhong-Hua; Wang, Jing-Xu; Gao, Shengnan; Sun, Jian; Liu, Guo-Ping (Information sciences, 2023)
The time-varying formation problem is addressed for second-order multi-agent systems with matched and mismatched disturbances. A time-varying formation prescribed performance control method is presented with improved collision avoidance and connectivity maintenance scheme. Specifically, more accurate judgment mechanisms of collision risks and connectivity interruption risks are proposed to reduce conservatism of the existing results, by making use of the velocity information and analyzing the maneuvering process of agents. Then, a nonlinear disturbance observer is adopted to estimate those disturbances, and an adaptive prescribed performance controller based on a novel performance function is developed to obtain the predesigned transient performance and steady-state performance. Finally, theoretical analysis, numerical simulation, and actual experiments are given to verify the proposed method. •Less conservative judgment mechanisms of collision risks and connectivity interruption risks are presented.•An adaptive controller is proposed to deal with matched and mismatched disturbances by using a disturbance observer.•The prescribed performance is achieved by designing a performance function based on the logistic function.•Simulation and experimental results demonstrate the effectiveness and advantage of the proposed method.